Employment Protection Deregulation and Labor Shares in Advanced Economies - Ciminelli, Gabriele; Duval, Romain; Furceri, Davide (Washington, D.C. : International Monetary Fund, 2018)
Labor market deregulation, intended to boost productivity and employment, is one plausible, yet little studied, driver of the decline in labor shares that took place across most advanced economies since the early 1990s. This paper assesses the impact of job protection deregulation in a sample of 26 advanced economies over the period 1970-2015, using a newly constructed dataset of major reforms to employment protection legislation for regular contracts. We apply the local projection method to estimate the dynamic response of the labor share to our reform events at both the country and the country-industry levels. For the latter, we employ a differences-in-differences identification strategy using two identifying assumptions grounded in theory-namely that job protection deregulation should have larger negative effects in industries characterized by (i) a higher 'natural' propensity to adjust the workforce, and (ii) a lower elasticity of substitution between capital and labor. We find a statistically significant, economically large and robust negative effect of deregulation on the labor share. In particular, illustrative back-of-the-envelope calculations suggest that job protection deregulation may have contributed about 15 percent to the average labor share decline in advanced economies. Together with existing evidence regarding the macroeconomic gains from job protection and other labor market reforms, our results also point to the need for policymakers to address efficiency-equity trade-offs when designing such reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet